Pembinaan Peningkatan Keterampilan Menggunakan Aplikasi Kasir Pintar Berbasis Android pada Masyarakat Tembesi Tower Batam - Yulia Yulia; Elva Susanti; Roni Chandra Tampubolon (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2019)
The use of mobile technology applications that are increasingly developing ultimately has a very positive impact on various fields of life, one of which is the field of commerce. However, rarely people know there is a smart cashier application because there is no advertise it, even though this smart cashier application is very easy for traders to determine profits every day, all transaction data will be recorded if we use the application. This application can make transactions that aim to input sales that are selling at the time and also if there is a merchant promotion that provides discounts (discounts) without having to calculate with a calculator and without fear of miscalculating. Tembesi Tower Community RT.03 / RW.16 Tembesi Village, Sagulung Subdistrict, Batam In particular, PKK Makmur Jaya mothers who have priority as trading entrepreneurs, such as having shops or stalls, selling food and so on. In general, Tembesi Tower people only use conventional media to count their merchandise in every transaction such as a calculator, so the level of consumer confidence is slightly reduced if the traders cannot calculate it correctly. Dedication is carried out with the aim to improve skills in the use of smart cashier applications as learning and reference in facilitating work aimed at the Tembesi Tower community in the Sagulung district of Batam.